In Search of Leading Indicators of Economic Activity in Germany - Harm Bandholz; Michael Funke (Center for Economic Studies and ifo Institute (CESifo), 2001)
In this paper we present two new composite leading indicators of economicactivity in Germany estimated using a dynamic factor model with and withoutregime switching. The obtained optimal inferences of business cycle turningpoints indicate that the two-state regime switching procedure leads to asuccessful representation of the sample data and provides an appropriatetool for forecasting business conditions.
Keywords: 330; business cycles; leading indicators; turning points; Markovswitching; Germany